2020
DOI: 10.1111/ijcp.13587
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for surgical margin status and recurrence in partial nephrectomy

Abstract: Purpose To evaluate the prognostic factors affecting the surgical margin and recurrence in patients who underwent partial nephrectomy (PN) for renal masses. Materials and Methods Data of 125 patients who underwent open or laparoscopic PN because of renal mass between January 2006 and January 2019 were analysed retrospectively. Demographic data, habits, additional diseases, clinical and laboratory findings, operational data, the morphology of the tumour in computerised tomography or magnetic‐resonance imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
1
1
1
Order By: Relevance
“…Interestingly, our study did not find a significant association between recurrence and other factors such as age, PADUA score, tumor stage, presence of necrosis, and resection technique. This contrasts with some studies that have suggested these factors may influence recurrence risk [11,25]. The lack of statistical significance in our study could be due to sample size or the distribution of these factors within our cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our study did not find a significant association between recurrence and other factors such as age, PADUA score, tumor stage, presence of necrosis, and resection technique. This contrasts with some studies that have suggested these factors may influence recurrence risk [11,25]. The lack of statistical significance in our study could be due to sample size or the distribution of these factors within our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…The Leibovich score, tumor size, and Fuhrmann grade, among other factors, were also significantly associated with recurrence in our study. This is in agreement with previous studies that have validated the Leibovich scoring system as a reliable predictor of recurrence in RCC [11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…Even though this study has one of the longest follow-up span in the literature, low number of cases can be asserted as the main limitation of this study. This study also has the feature of being supplementary to our recent study about the prognostic factors indicating surgical margin status and recurrence in partial nephrectomy patients [29]. The number of patients have increased throughout the years, enriching this study.…”
Section: Discussionmentioning
confidence: 72%